Issues in prisons - Healey, Justin (Issues in society (Balmain, N.S.W.), 2017)
Why are prison numbers rising in Australia, and what are the alternatives to imprisonment? This book examines imprisonment rates and criminal justice reform options. Is the incarceration of offenders deterring them from re-offending and reducing crime rates? What are the human and financial costs of imprisonment, especially for detained young people and Indigenous Australians? How can we work towards more effective rehabilitation, crime reduction and justice reinvestment? Also includes: worksheets and activities, fast facts, glossary, web links, index.